Photonic topological Anderson insulator in a two-dimensional atomic lattice - Skipetrov, Sergey E.; Wulles, Pierre (Comptes Rendus. Physique)
Disorder in atomic positions can induce a topologically nontrivial phase—topological Anderson insulator (TAI)—for transverse electric optical quasimodes of a two-dimensional honeycomb lattice of immobile atoms. TAI requires both time-reversal and inversion symmetries to be broken to similar extents. It is characterized by a nonzero topological invariant, a reduced density of states and spatially localized quasimodes in the bulk, as well as propagating edge states. A transition from TAI to the topological insulator (TI) phase can take place at a constant value of the topological invariant, showing that TAI and TI represent the same topological phase.